1986
DOI: 10.1021/bk-1986-0294.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Amino Acid Metabolism During Exercise

Abstract: Athletes associate performance with diet. Meat became a staple of ancient Greek and Roman athletes as they attempted to achieve the strength and endurance of carnivorous members of the animal kingdom. As knowledge of nutrition and muscle physiology increased, athletes became convinced that to increase muscle mass and strength required increased dietary protein. However, nutrition textbooks (1,2) and the Recommended Dietary Allowances (RDA's) established by the National Academy of Sciences (3) state that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Henderson et al (33) confirmed this training effect on leucine oxidation using in vivo measures (Figure 13). Probably these adaptations are due to an increased amount of the branched-chain ketoacid dehydrogenase in the active form, because traininginduced increases of the enzyme have been measured in both muscle and liver ( Figure 14) (44). Unless a compensatory decrease (below baseline) in oxidation occurs between training sessions, these data indicate that chronic endurance exercise is likely to elevate daily requirements for leucine.…”
Section: Endurance Exercisementioning
confidence: 94%
“…Henderson et al (33) confirmed this training effect on leucine oxidation using in vivo measures (Figure 13). Probably these adaptations are due to an increased amount of the branched-chain ketoacid dehydrogenase in the active form, because traininginduced increases of the enzyme have been measured in both muscle and liver ( Figure 14) (44). Unless a compensatory decrease (below baseline) in oxidation occurs between training sessions, these data indicate that chronic endurance exercise is likely to elevate daily requirements for leucine.…”
Section: Endurance Exercisementioning
confidence: 94%
“…19, NO. 5 changes in branched-chain oxoacid dehydrogenase activity [38]; however, more study is required, as at least one study doesn't support these data [39] and there is no apparent explanation for these contradictory observations. With strength training there is also some confusion.…”
Section: Smentioning
confidence: 99%
“…Although considerable debate has gone on for years (Cathcart 1925, Lemon 1987, Butterfield 1991, Hickson and Wolinsky 1994, Layman et al 1994, Poortmans 1994, Rennie et al 1994a, recent scientific data indicate that dietary protein intake in excess of the current RDA is likdy needed for optimal muscle growth. However, the benefit appears to plateau at intakes well below the intakes typically consumed by many athletes.…”
Section: Heavy Resistance Exercisementioning
confidence: 99%